A Differentiated and Integrated Learning Strategy: Science, Technology, Engineering, and Mathematics-Education for Sustainable Development Project Based on Students’ Learning Style - Liandha Arieska Putri; Toru Matsumoto; Ida Kaniawati; Anna Permanasari; Diana Rochintaniawati; Indriyani Rachman (Jurnal Pendidikan Sains Indonesia, 2026)
The increasing world energy demand and the depletion of natural energy supplies encourage the need to integrate a sustainable lifestyle. Following the Indonesian independent curriculum, teaching and learning have to incorporate both differentiated and integrated learning. This study investigates the accommodation of students' needs based on their learning style in STEM-ESD PjBL as an integrated and differentiated learning strategy. This research used a qualitative descriptive research method and included 19 junior high school students as participants. The result highlighted that the learning model accommodated diverse students’ needs and contributed positively to learning motivation. Effective implementation requires teachers to provide appropriate learning supports, such as visual representation for visual learners, discussion-based activities for aural learners, printed or text-based learning material for read/write learners, and hands-on activities for kinesthetic learners. Furthermore, group composition was found to be most effective when it included a balanced distribution of learning styles, with at least one representative of each VARK modality to facilitate collaboration, coordination, and group leadership